An Emotion-Driven Vocal Biomarker-Based PTSD Screening Tool - Thomas F. Quatieri; Jing Wang; James R. Williamson; Richard DeLaura; Tanya Talkar; Nancy P. Solomon; Stefanie E. Kuchinsky; Megan Eitel; Tracey Brickell; Sara Lippa; Kristin J. Heaton; Douglas S. Brungart; et al. (IEEE Open Journal of Engineering in Medicine and Biology)
Goal: This paper introduces an automated post-traumatic stress disorder (PTSD) screening tool that could potentially be used as a self-assessment or inserted into routine medical visits to aid in PTSD diagnosis and treatment. Methods: With an emotion estimation algorithm providing arousal (excited to calm) and valence (pleasure to displeasure) levels through discourse, we select regions of the acoustic signal that are most salient for PTSD detection. Our algorithm was tested on a subset of data from the DVBIC-TBICoE TBI Study, which contains PTSD Check List Civilian (PCL-C) assessment scores. Results: Speech from low-arousal and positive-valence regions provide the highest discrimination for PTSD. Our model achieved an AUC (area under the curve) of 0.80 in detecting PCL-C ratings, outperforming models with no emotion filtering (AUC = 0.68). Conclusions: This result suggests that emotion drives the selection of the most salient temporal regions of an audio recording for PTSD detection.